Electric Vehicle Technologies in the Smart Grid Era: A Comprehensive Review - Shady S. Refaat; Amira Mohammed; Tareq Foqha; Ahmed Syed; Samer Alsadi; Mostafa Farrag (IET Electrical Systems in Transportation)
Electric vehicles (EVs) present an efficient solution for reducing greenhouse gas (GHG) emissions and enhancing grid power quality. They offer multiple advantages over traditional internal combustion engines (ICEs), including lower emissions, reduced dependance on oil, higher energy efficiency, quieter operation, zero emissions, and improved air quality by minimizing the release of toxic chemicals into the atmosphere. However, there is a lack of literature that comprehensively reviews the factors that can facilitate the assimilation of EV technology. Therefore, this paper provides a comprehensive review of EV technologies, focusing on the growth of global EV adoption and the various types of EVs, including all-EVs and hybrid EVs (HEVs). The comparative analysis of different HEV technologies is presented, covering full HEVs, mild HEVs, and plug-in HEVs (PHEVs). The paper also discusses the different classifications of HEVs based on electrification level and energy source, along with a comparative analysis of their configurations. Furthermore, the EV architecture is examined, with a specific focus on electric motors, battery management systems (BMSs), batteries, and charging technologies, including conductive and wireless charging systems. The challenges in EV charging and the associated charging standards are also addressed. The paper concludes by highlighting the need for the advancement of EV technologies and infrastructure to overcome the significant barriers to rapid EV adoption, while demonstrating how smart grid technologies enhance EV charging efficiency, grid resilience, and energy sustainability.